KELUARGA SAKINAH PERSPEKTIF MAHASISWA YANG SUDAH MENIKAH - Hasiah . (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2021)
We find that in almost all public and private universitiesin Indonesia, several married students are found. Students who decide to get married eill be facedwith conditions where they should be contrindicated to complete academics, graduate early, then get a job, must be able to manage time, shareenergy and take care of the family. Students wh get married while in college, of course have strong reasons, have the motivation and drive to get married durring their studies.In this study, researchers used a qualitative descriptive methode with data collection techniques through observation, interviews or direct interviews with informants. Sampling conducted by researchers with purposive sampling. And the focus of this research is the Padangsidimpuan State Islamic Institutestudents who are registered as active and marriedstudents.The results of the study informed that the motivation of students who got marriedat the timeof study was fear of sin, the existence of compatibility and mutual need, feeling that they had been obliged to marry (old enough), there was guidance from others.